2006
DOI: 10.1007/s12110-006-1003-1
|View full text |Cite
|
Sign up to set email alerts
|

Height and reproductive success

Abstract: Publisher's copyright statement:The original publication is available at www.springerlink.com Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 38 publications
1
36
1
Order By: Relevance
“…This is no different from the proportion of female-taller marriages expected by chance (8.8%: Figure 1 shows the proportion of female-taller marriages in this Hadza population. R. S. has previously investigated this phenomenon in both a post-industrial society (UK) and a pre-industrial agricultural community in the Gambia, and the results of these analyses are also presented in figure 1 for comparison (Sear 2006). The proportion of female-taller marriages in the UK is significantly lower than expected by chance, but the two traditional populations show a frequency of female-taller relationships no different from that expected from mating which is random with respect to height.…”
Section: Results (A) Assortative Matingmentioning
confidence: 99%
“…This is no different from the proportion of female-taller marriages expected by chance (8.8%: Figure 1 shows the proportion of female-taller marriages in this Hadza population. R. S. has previously investigated this phenomenon in both a post-industrial society (UK) and a pre-industrial agricultural community in the Gambia, and the results of these analyses are also presented in figure 1 for comparison (Sear 2006). The proportion of female-taller marriages in the UK is significantly lower than expected by chance, but the two traditional populations show a frequency of female-taller relationships no different from that expected from mating which is random with respect to height.…”
Section: Results (A) Assortative Matingmentioning
confidence: 99%
“…One possibility is competition between surviving offspring for later reproductive opportunities. For example, several studies have shown that fertility is negatively associated with offspring height [46,55], which may ultimately reduce adult reproductive success in both sexes [56]. Yet, current literature suggests that siblings only depress marital and reproductive success in situations where material wealth is transferred across generations, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…All of these factors could allow some parents to invest more in both reproductive rate and parental investment, while nevertheless remaining subject to allocation trade-offs. Female physical condition is also clearly important; it is now well established that in many populations children of tall mothers experience significantly lower mortality [55,56].…”
Section: (B) Socioecological Contextmentioning
confidence: 99%